Health Service Seeking Behavior among Migrant Workers in Small and Medium-Sized Enterprises in Guangdong, China: Does Family Migration Matter?. (21st November 2018) - Dang, Yuewen; Zou, Guanyang; Peng, Boli; Ling, Li
Abstract : Objective . This study aims to understand the health service seeking behavior of migrant workers and explore its association with their living status (i.e., living with family members or not), in Guangdong, China. Methods . This was a cross-sectional survey conducted with 912 migrant workers in 2012 using a structured questionnaire adapted from the National Health Service Survey. Data were analyzed using the multivariable logistic regression. Results . Of all migrant workers, 58% lived with at least one family member in the host city. Most of the respondents rated their health status being "very good or good" (58%). Fifty-four percent of the respondents reported having at least one disease in the past 12 months. Sixty-two percent of those who reported at least one disease visited doctors in the past 12 months. Of these, 22% returned to their hometown for medical treatment. Logistic regression showed that migrant workers living with families rated themselves as having better health status ( P <0.05) but had more diseases ( P >0.05) and had higher doctor visitation rate than those living with alone (58% vs. 66%, P <0.05). Conclusion . The Andersen health service utilization model helps to understand the health seeking behavior of the migrant workers in the host cities. Migrant workers living with family members were positively associated with self-rated health status and health service seeking behavior in small and medium-sized enterprises. Our findings suggest the importance of the assistance programs and social support to improve seeking of healthcare services among migrant groups, especially those who live alone in the host cities.